2005
DOI: 10.1111/j.1525-1497.2005.0174.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of limited English proficiency and physician language on health care comprehension

Abstract: OBJECTIVE:To determine the effect of limited English proficiency on medical comprehension in the presence and absence of language-concordant physicians. DESIGN, SETTING, AND PARTICIPANTS:A telephone survey of 1,200 Californians was conducted in 11 languages. The survey included 4 items on medical comprehension: problems understanding a medical situation, confusion about medication use, trouble understanding labels on medication, and bad reactions to medications. Respondents were also asked about English profic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
330
3
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(384 citation statements)
references
References 43 publications
10
330
3
10
Order By: Relevance
“…Language barriers play a significant role in poor health processes and outcomes, [4][5][6][7] including reduced accessing of preventive services 8,9 and cancer screening rates among LEP patients. [10][11][12][13] These obstacles to cancer screenings for LEP patients can be reduced with language assistance. Patient navigation is a promising intervention to eliminate language as a barrier to cancer screening for LEP patients.…”
Section: Introductionmentioning
confidence: 99%
“…Language barriers play a significant role in poor health processes and outcomes, [4][5][6][7] including reduced accessing of preventive services 8,9 and cancer screening rates among LEP patients. [10][11][12][13] These obstacles to cancer screenings for LEP patients can be reduced with language assistance. Patient navigation is a promising intervention to eliminate language as a barrier to cancer screening for LEP patients.…”
Section: Introductionmentioning
confidence: 99%
“…We used the literature and prior studies to determine the most parsimonious models given sample size considerations. 4,5 We conducted post hoc analyses to determine whether including household income or the number of medications attenuated the effect size or changed the direction of the association with each outcome measure. Table 1 reports weighted patient demographics and clinical characteristics for all survey respondents stratified by LEP status.…”
Section: Methodsmentioning
confidence: 99%
“…3 However, research on the use of refill functions of SMRs is scarce among patients whose primary language is not English. Patients with limited English proficiency and chronic conditions are at increased risk of medication nonadherence 4,5 and receive lower-quality care than patients who are proficient in English. [6][7][8] One study suggested that patient use of an online portal with refill function increased adherence to statin medications for those with diabetes receiving care in an integrated health system.…”
Section: Introductionmentioning
confidence: 99%
“…109 Having language-concordant clinicians with training in medical interpretation is ideal, 110 but organizations should at least offer access to certified medical interpreters to facilitate SDM. 43 A lack of professional medical interpretation services leads to errors in diagnosis and treatment, decreases patient satisfaction and continuity of care, and increases distrust.…”
Section: Language and Medical Interpretation Servicesmentioning
confidence: 99%
“…43 A lack of professional medical interpretation services leads to errors in diagnosis and treatment, decreases patient satisfaction and continuity of care, and increases distrust. [109][110][111] Organizations should also avoid using patients' family members as interpreters, which can compromise patient privacy, introduce interpretation errors, and possibly harm family relationships. 43 This could be particularly problematic for LGBT patients who have not disclosed their sexual orientation or gender identity to family members and need additional privacy for successful SDM.…”
Section: Language and Medical Interpretation Servicesmentioning
confidence: 99%